Proline Accumulation and Physiological Responses of Indica Rice Genotypes Differing in Tolerance to Salt and Drought Stresses - Chutipaijit, Sutee (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2010)
The study determined the relationship between proline accumulation and physiological responses of indica rice genotypes to salt and drought stresses in photoautotrophic conditions. Two salt-tolerant genotypes of indica rice [cv. jasmine rice (KDML 105) and Dang], two drought-tolerant genotypes [Rice Department 6 (RD6) and Rice Department 15 (RD15)] and a salt-and drought-sensitive genotype [Pathumthani 1 (PT 1)] were exposed to 100 mM NaCl (salt stress) or 100 mM mannitol (drought stress) for 4 d. The relative water content (RWC) and malondialdehyde (MDA) accumulation in salt-and drought-tolerant genotypes did not significantly change. The proline accumulation in these genotypes greatly increased with stress. On the other hand, the salt-and drought-sensitive genotype which had lower proline accumulation demonstrated a significant decrease in RWC and increase in MDA content. Moreover, our results showed a strong correlation between proline concentrations and free radical scavenging by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. The high concentration of proline solution presented high DPPH antioxidant activity. The higher proline accumulation in stressed seedlings of tolerant genotypes may help to maintain the RWC and MDA of rice plant, which could lead to preferable growth performance.